La mise en œuvre des corridors écologiques : de la concertation locale à l’inscription foncière communale - Raphaëlle Cormerais-Thomin; Nathalie Bertrand (Développement Durable et Territoires)
The Grenelle II law (2010) has promoted by the inclusion of a Green and Blue infrastructure in planning documents, as a new planning tool to preserve biodiversity and restore ecological continuities, especially within urban regions. This article will show - on the basis of a Rhône-Alpes research - how the implementation of ecological corridors varies according to the municipal and supra-municipal consultation process. The analysis is based on the one hand on a broader vision of consultation processes, on the other hand, on the connexion between ecological corridors within planning documents and regulation of agricultural land use.